2013
DOI: 10.1007/s00264-013-1964-8
|View full text |Cite|
|
Sign up to set email alerts
|

Different thermal conductivity in drilling of cemented compared with cementless hip prostheses in the treatment of periprosthetic fractures of the proximal femur—an experimental biomechanical analysis

Abstract: Purpose The purpose of this study was to evaluate the different temperature levels whilst drilling cemented and cementless hip prostheses implanted in bovine femora, and to evaluate the insulating function of the cement layer. Methods Standard hip prostheses were implanted in bovine donor diaphyses, with or without a cement layer. Drilling was then performed using high-performance-cutting drills with a reinforced core, a drilling diameter of 5.5 mm and cooling channels through the tip of the drill for constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
4
0
2
Order By: Relevance
“…Periprosthetic screws must sometimes be inserted in cement, especially when proximal and surrounding a HA. It has been proven that cement is not affected by these screws [28,29] as the heat produced by drilling is harmless [30]. In presence of an intramedullary implant, one must bridge it to avoid stress fracture on a weak spot [31] and must be bridged by the length of two diaphyseal diameters [11].…”
Section: Discussionmentioning
confidence: 99%
“…Periprosthetic screws must sometimes be inserted in cement, especially when proximal and surrounding a HA. It has been proven that cement is not affected by these screws [28,29] as the heat produced by drilling is harmless [30]. In presence of an intramedullary implant, one must bridge it to avoid stress fracture on a weak spot [31] and must be bridged by the length of two diaphyseal diameters [11].…”
Section: Discussionmentioning
confidence: 99%
“…Using a custom-made internal cooling device within the power drill setup reduced temperatures during drilling to tissue-preserving levels for cemented hip stems (24.7 °C) [ 45 ]. However, the same research group also demonstrated that for cementless hip stems without the insulating cement layer, the temperature during drilling increased to 47 °C, even when the internal cooling device was applied [ 46 ]. These studies indicate a potential solution for the concern of tissue-preservation during transprosthetic drilling, with however some further research being required especially for cementless hip stems.…”
Section: Potential For Future Developments In Vancouver B1 and C Fracmentioning
confidence: 99%
“…Concerns about high drilling temperatures potentially causing osteonecrosis could be sorted out. 29,30 However, the impact of drilling the hip stem on implant integrity has not been investigated yet. Drill holes may weaken the strength of the prosthesis, potentially leading to material failure and breaking of the prosthesis.…”
Section: Introductionmentioning
confidence: 99%